Childhood Memory, Family Dynamics, and Rumination: A Systematic Review in a Psychological Perspective - Marita, Prily Carla; Hendriani, Wiwin (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The family is included in the smallest and closest circle to an individual. Family becomes the first environment to interact with an individual. Not all children go through a childhood full of laughter; some experience challenging childhoods, often referred to in psychology as adverse childhood experiences. This study aimed to analyze the influence of childhood memories and family dynamics on rumination tendencies through a systematic review, in order to understand the underlying psychological factors and the role of emotional memory in repetitive thinking among individuals. This study employed a systematic literature review method, with data collected from four journal portals: one national journal and three international journals. The national journal portal used was Garuda, with the search keywords